Progress in the Diagnosis of Invasive Fungal Disease in Children - Warris, Adilia (Curr Fungal Infect Rep, 2017)
PURPOSE OF REVIEW: This review summarizes the fungal diagnostic measures currently available for use in paediatric patients at high risk for developing invasive fungal disease (IFD) and those suspected of having an IFD. The clinical utility of each test is described based on reported performances of individual tests in specific paediatric populations. RECENT FINDINGS: Available studies in the paediatric population are scarce and are characterized by a huge heterogeneity in underlying diseases (e.g. different risk for IFD), different study objectives and management strategies (screening versus diagnostic) used. SUMMARY: A final valuation of paediatric studies on fungal diagnostic tools is limited. While the galactomannan and fungal PCR assays are useful to exclude the presence of IFD, it is unclear if mannan, mannan antibodies and β-D-glucan are of benefit due to a lack of studies or validation of the cut-off, respectively. Well-designed multicentre paediatric studies are urgently needed to improve the outcome of IFD.